(untitled) (Liberosis: Jurnal Psikologi dan Bimbingan Konseling, 2025)
Children with Attention Deficit Hyperactivity Disorder (ADHD) often experience obstacles in the learning process due to attention deficit disorder, hyperactivity, and impulsivity that they experience. These obstacles have a direct impact on their low learning motivation and academic achievement. This study aims to examine various learning strategies that have been proven effective in increasing the learning motivation of children with ADHD through a systematic review of scientific literature. The results of the study indicate that strategies such as providing clear instructions, breaking down tasks into small parts, positive reinforcement, the use of Individualized Education Programs (IEP), and metacognitive approaches can have a positive impact on the engagement and learning motivation of children with ADHD. Positive reinforcement-based approaches, such as praise or rewards, have been shown to significantly increase the duration of children’s learning focus. In addition, the use of interactive and game-based learning strategies helps create a fun and inclusive learning atmosphere. This study also highlights the importance of the role of teachers, parental involvement, and school environmental support in forming an adaptive learning ecosystem. In conclusion, the success of education for children with ADHD depends not only on the learning strategies used, but also on the collaboration of all parties in creating a positive learning environment that is responsive to their needs. Anak dengan Attention Deficit Hyperactivity Disorder (ADHD) sering mengalami hambatan dalam proses belajar akibat gangguan perhatian, hiperaktivitas, dan impulsivitas yang mereka alami. Hambatan ini berdampak langsung pada rendahnya motivasi belajar dan pencapaian akademik mereka. Studi ini bertujuan untuk menelaah berbagai strategi pembelajaran yang telah terbukti efektif dalam meningkatkan motivasi belajar anak ADHD melalui tinjauan sistematis terhadap literatur ilmiah. Hasil kajian menunjukkan bahwa strategi seperti pemberian instruksi yang jelas, pemecahan tugas menjadi bagian-bagian kecil, penguatan positif, penggunaan Individualized Education Program (IEP), serta pendekatan metakognitif mampu memberikan dampak positif terhadap keterlibatan dan motivasi belajar anak ADHD. Pendekatan berbasis penguatan positif, seperti pujian atau hadiah, terbukti meningkatkan durasi fokus belajar anak secara signifikan. Selain itu, penggunaan strategi pembelajaran yang interaktif dan berbasis permainan membantu menciptakan suasana belajar yang menyenangkan dan inklusif. Penelitian ini juga menyoroti pentingnya peran guru, keterlibatan orang tua, serta dukungan lingkungan sekolah dalam membentuk ekosistem pembelajaran yang adaptif. Kesimpulannya, keberhasilan pendidikan anak ADHD tidak hanya bergantung pada strategi pembelajaran yang digunakan, tetapi juga pada kolaborasi semua pihak dalam menciptakan lingkungan belajar yang positif dan responsif terhadap kebutuhan mereka.